Illness meanings and experiences for pre-ulcer and ulcer conditions of Buruli ulcer in the Ga-West and Ga-South Municipalities of Ghana - Ackumey Mercy M; Gyapong Margaret; Pappoe Matilda; Kwakye-Maclean Cynthia; Weiss Mitchell G (BMC, 2012)
Abstract Background Ghana is a Buruli ulcer (BU) endemic country yet there is paucity of socio-cultural research on BU. Examining distinctive experiences and meanings for pre-ulcers and ulcers of BU may clarify the disease burden, illness experience and local perceptions of causes and spread, and environmental features of BU, which are useful to guide public health programmes and future research. This study aimed to explain local meanings and experiences of BU for persons with pre-ulcers and ulcers in the Ga-West and Ga-South municipalities in Accra. Methods Semi-structured interviews based on the Explanatory Model Interview Catalogue framework were administered to 181 respondents comprising 15 respondents with pre-ulcers and 166 respondents with ulcers. The Wilcoxon rank-sum test was used to compare categories of illness experiences (PD) and perceived causes (PC) among respondents with pre-ulcer and ulcer conditions. The Fisher's exact test was used to compare the most troubling PD and the most important PC variables. Qualitative phenomenological analysis of respondents' narratives clarified illness experiences and meanings with reference to PC and PD variables. Results Families of respondents with pre-ulcers and the respondents themselves were often anxious about disease progression, while families of respondents with ulcers, who had to give care, worried about income loss and disruption of school attendance. Respondents with pre-ulcers frequently reported swimming in ponds and rivers as a perceived cause and considered it as the most important PC (53.3%). Respondents with ulcers frequently attributed their BU illness to witchcraft (64.5%) and respondents who claimed they had no water contact, questioned the credibility of health messages Conclusions Affected persons with pre-ulcers are likely to delay treatment because of social and financial constraints and the absence of pain. Scepticism on the role of water in disease contagion and prolonged healing is perceived to make ideas of witchcraft as a PC more credible, among respondents with ulcers. Health messages should address issues of locally perceived risk and vulnerability. Guided by study findings, further research on the role of environmental, socio-cultural and genetic factors in BU contagion, is also needed to clarify and formulate health messages and strengthen public health initiatives.